An association between genetic variation in the glutamatergic system and suicide attempts in alcohol‐dependent individuals. (30th May 2017) - Fudalej, Sylwia; Klimkiewicz, Anna; Mach, Anna; Jakubczyk, Andrzej; Fudalej, Marcin; Wasilewska, Krystyna; Podgórska, Anna; Krajewski, Paweł; Płoski, Rafał; Wojnar, Marcin
Abstract : Background and Objectives: Pathological alterations of glutamatergic systems were observed in neurodegenerative and psychiatric disorders. There is some evidence that this system may be involved in the genetic vulnerability to suicide. The aim of the present study was to analyze possible relationship between the GRIN2B polymorphism and suicidal behavior. We hypothesized that this genetic factor may be associated with suicide attempts in alcohol‐dependent patients and with death by suicide. Methods: To analyze the relationship between GRIN2B and suicide attempts, the selected rs2268115 polymorphism was genotyped in a sample of 345 alcohol‐dependent individuals stratified by the history of suicide attempts. The second part of the study concerning suicide was based on a sample of 510 suicide victims and 450 controls. Results: The frequency of rs2268115 G allele among alcohol‐dependent patients with the history of suicide attempts was significantly higher than among non‐suicidal alcohol‐dependent individuals (OR = 1.45, p  = .033). This association was more significant when analyzing alcohol‐dependent patients only without co‐occurring drug dependence (OR = 1.62, p  = .021). The analyzed GRIN2B polymorphism was associated with a twofold increase in odds of a suicide attempt (OR = 2.01, p  = .004). No relationships between rs2268115 and death by suicide were identified. Discussion and Conclusions: Our results suggest that glutamatergic system influence susceptibility to suicide attempts in alcohol‐dependent individuals. Suicidal behavior and alcohol dependence may share a common etiology related to the glutamatergic system. Scientific Significance: The major contribution of the present study is a novel finding of the possible association between GRIN2B rs2268115 polymorphism and suicide attempts in alcohol‐dependent individuals. (Am J Addict 2017;26:595–601)